Pengembangan Media Pop Up Book Fashion sebagai Media Pembelajaran di SMK Negeri 6 Surabaya (International Forum of Researchers and Lecturers, 2025)
This research is motivated by the lack of interesting learning media that can motivate and facilitate students in understanding fashion design material. The purpose of this research is to develop Pop-Up Book Fashion media as an innovative and interactive learning tool and to determine the feasibility of Pop-Up Book Fashion media on the material of custom skirts. The research method used is development research with a 4D model with stages consisting of 4 main stages, namely: (1) Define (Definition) (2) Design (Planning); (3) Develop (Development); (4) Disseminate (Dissemination). Assessment of product feasibility results is carried out by validation to 1 validator, namely a media expert. There is 1 more validator, namely the validator of the student response questionnaire instrument. Based on the value of the validator regarding the results of the product feasibility, the average score from the media expert is 91% (very feasible). Trials on 18 class X students of SMK Negeri 6 Surabaya showed an interest level of 91.11% (very interesting). So it can be concluded that the Pop up book Fashion media is proven to be effective and interesting to use as a learning medium. This media is recommended as an innovative alternative to improve student learning outcomes, particularly in fashion design. In addition to enhancing students' understanding of fashion design materials, the use of Pop-Up Book Fashion media also provides a stronger visual and kinesthetic learning experience. Through direct interaction with media that can be touched and moved, students can imagine the final form of clothing more realistically, especially for the custom skirt material that requires visualization of models and construction. This media not only helps with cognitive aspects but also facilitates students' emotional engagement in the learning process. This is in line with the thematic learning approach that emphasizes the importance of multisensory engagement in increasing retention and learning interest.